The Role of Micro Entrepreneurship in Poverty Alleviation for Refugees in Turkey - Olfat Aldalou; Abdalrahman Migdad (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
Considering recent global economic and environmental crises following the Syrian war and the influx of large numbers of displaced people to Turkey, and with the rise in poverty and the difficulty of life, many small projects were undertaken to alleviate poverty and provide a means of subsistence. Micro entrepreneurs offer job opportunities to people, especially those with low incomes, and provide more goods and services to the public. The study aims to investigate the impact of micro-entrepreneurship on poverty alleviation and highlight the most significant obstacles facing owners of small-scale projects and solutions to enhance their effective impact. The data was collected through 113 questionnaires to micro-business owners through the random sampling method. The results showed that the projects improve the living conditions for individuals and have a positive impact on economic recovery despite the obstacles and restrictions imposed considering the deteriorating economic situation.